2021
DOI: 10.3390/buildings11120576
|View full text |Cite
|
Sign up to set email alerts
|

Shear Behavior of Reinforced Post-Filling Coarse Aggregate Concrete Beams Produced by Creative Construction Process

Abstract: Different from the traditional concrete mixing procedure, the innovative post-filling coarse aggregate concrete (PFCC) reduces the cost of pumping concrete by increasing the coarse aggregate content and reducing the usage of cement. Previous studies have shown that PFCC enhances the compressive strength, elastic modulus, and flexural strength of concrete. In this paper, the shear behavior of 13 post-filling coarse aggregate concrete beams and 3 control beams was tested to determine the relationships between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…When under small eccentric compression, the column with a 10% PFR had the best ductility, whereas for large eccentric compression, the highest ductility of the column appeared at a PFR of 20%. In a study of PFCC beam specimens, it was found that the shear resistance of the beam reached its maximum at a PFR between 10% and 15% [17], whereas the optimal flexural resistance appeared at a PFR of 20%. In some tests [17], it was found that the cement used in the PFCC was 90% of the reference concrete, which saved 10% cement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When under small eccentric compression, the column with a 10% PFR had the best ductility, whereas for large eccentric compression, the highest ductility of the column appeared at a PFR of 20%. In a study of PFCC beam specimens, it was found that the shear resistance of the beam reached its maximum at a PFR between 10% and 15% [17], whereas the optimal flexural resistance appeared at a PFR of 20%. In some tests [17], it was found that the cement used in the PFCC was 90% of the reference concrete, which saved 10% cement.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of PFCC beam specimens, it was found that the shear resistance of the beam reached its maximum at a PFR between 10% and 15% [17], whereas the optimal flexural resistance appeared at a PFR of 20%. In some tests [17], it was found that the cement used in the PFCC was 90% of the reference concrete, which saved 10% cement.…”
Section: Introductionmentioning
confidence: 99%
“…Its flexural performance increases first and then decreases with the increase of post‐filling ratio, reaching the best at 20%. Jia et al 24 also studied the effect of volume replacement ratio, strength grade of concrete, shear span ratio, volume‐stirrup ratio on the shear performance and results shows that 25 the post‐filling aggregate process can reduce the porosity and increase the concrete strength by reducing the effective water binder ratio and increasing the volume fraction of aggregate, among which the effect of increasing the volume fraction of aggregate is more significant. When the concrete strength grade is certain, the ultimate bearing shear force of the beam as a whole increases first and then decreases with the increase of the post‐filling ratio, reaching the peak at 15%.…”
Section: Introductionmentioning
confidence: 99%
“…Although the basic properties, flexural and shear properties of beams as well as axial compression and eccentric compression of columns specimens have been investigated, 1,[22][23][24][25][26] the seismic behavior of beam-column joint made of post-filling coarse aggregate concrete has not been reported. It is crucial to study and understand the seismic behavior of post filling coarse aggregate to facilitate its application in engineering.…”
Section: Introductionmentioning
confidence: 99%